Gagal Napas Akut Tipe II pada Pasien Penyakit Paru Obstruktif Kronik (PPOK) Eksaserbasi Akut yang Diterapi dengan High Flow Nasal Cannula (HFNC): Laporan Kasus: Laporan Kasus - Rahardjo, Abdi Malik; Mukhlis, Mokhammad (Cermin Dunia Kedokteran, 2026)
Introduction: Acute respiratory failure is a condition seen in respiratory system failure to supply gas exchange, oxygenation, and elimination of carbon dioxide (CO2) processes that occurs in minutes or hours. Case: A 57-year-old male came to the emergency room with complaints of shortness of breath since 5 days ago, worsened during light activities. The patient also complained of worsening cough since 5 days ago, accompanied by thick yellowish-white phlegm. History of smoking 12 sticks/day since the age of 20 years and quit 5 years ago. Diagnosis was acute respiratory failure type II and the cause was chronic obstructive pulmonary disease (COPD) acute exacerbation. The management is high flow nasal cannula (HFNC) with FiO2 80%, because HFNC has an additional heating and humidification system that makes it more comfortable. Discussion: Alveolar hypoventilation and increased minute ventilation in COPD patients may carry a type II acute respiratory failure risk. Conclusion: Type II acute respiratory failure commonly occurs in patients with chronic respiratory diseases such as COPD. High flow nasal cannula (HFNC) oxygen therapy may be the best option.